Čas kolere Epidemije kolere na Kranjskem v 19. stoletju - Keber, Katarina (Thesaurus memoriae, 2007)
The book discusses all five cholera epidemics that hit the central Slovenian area in 1836, 1849, 1855, 1866, and 1886. It is the first synthesis of cholera epidemics and the first presentation of the health conditions in the 19th-century Carniola.Largely drawing on original archival materials, the book also provides Slovenian historiography with new and original knowledge, and substantially places itself side by side other European and American historiographical research dealing with the phenomenon of cholera epidemics in health, social, cultural and political context.